Unsur Jarîmah Qadhaf dalam Penetapan Status Hukum Anak Luar Kawin - M. Nurul Irfan (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: The Jarîmah Qadhaf in Determining the Legal Status of Illegitimate Children. The decision of South Jakarta Religious Court which compared a child born within an unregistered marriage with a child born outside marriage are equal is a real form of rejection of the plaintiff’s claim in a lawsuit of the legal status of illegitimate children. From an Islamic criminal law perspective, determining the legal status of illegitimate children contains an element of jarîmah qadhaf or the criminal act of adultery which is prohibited in Q.s. al-Nûr [24]: 4. The legal process in this case still proceeding after the plaintiff expressed an intention to continue to the appeals process at the Jakarta PTA level and if necessary up to the level of the Supreme Court of Cassation. In the process of seeking justice, this will certainly bring benefits to the discourse and dynamics of Islamic family law in the future.Keywords: jarîmah, qadhaf, claim, illegitimate children, children of adulteryAbstrak: Unsur Jarîmah Qadhaf dalam Penetapan Status Hukum Anak Luar Kawin. Putusan Pengadilan Agama Jakarta Selatan yang menganggap sama antara anak yang lahir akibat perkawinan tidak tercatat dengan anak lahir di luar perkawinan merupakan sebuah bentuk nyata penolakan gugatan pihak penggugat dalam perkara gugatan status hukum anak luar kawin. Dalam perspektif hukum Pidana Islam, penetapan status hukum anak luar kawin ini mengandung unsur jarîmah qadhaf atau tindak pidana menuduh zina yang dilarang dalam Q.s. al-Nûr [24] ayat 4. Proses hukum dalam perkara ini masih terus bergulir setelah pihak penggugat menyatakan pikir-pikir untuk kemudian diteruskan pada proses banding ke tingkat PTA DKI Jakarta dan jika perlu hingga pada tingkat Kasasi Mahkamah Agung RI. Dalam proses pencarian keadilan ini dipastikan akan membawa manfaat bagi wacana dan dinamisasi hukum keluarga Islam di di masa-masa yang akan datang.Kata Kunci: jarîmah, qadhaf, gugatan, anak luar kawin, anak zinaDOI: 10.15408/ajis.v13i2.935